Morphometric and phylogenetic analysis of a commercial fish Leiognathus equula (Teleostei, Leiognathidae) - Jiajie Chen; Xiaodong Wang; Sheng Zeng; Wei Tian; Deyuan Yang; Jinqing Ye; Junsheng Zhong; Chaopeng Jiang (ZooKeys)
The complete mitochondrial genome and phylogenetic analysis for Leiognathus equula from the South China Sea was performed using shallow genome skimming. For accurate species identification and redescription, morphometric and meristic characters were examined and compared with previous descriptions. To facilitate the identification of species and to enable comparison with the mitochondrial genome phylogeny, molecular comparisons were conducted using three mitochondrial genes: large ribosomal RNA (16S rRNA), cytochrome c oxidase subunit 1 (COX1), and NADH dehydrogenase (ND5). The mitogenome (16 398 bp) comprised 38 mitochondrial genes, similar to most bony fishes: 13 protein-coding genes (PCGs), 2 rRNA and 22 transfer RNA genes, and 1 non-coding region. The complete mitogenome comprised 30.7% A, 24.2% T, 15.0% G, and 30.1% C. The A+T content (54.9%) was higher than the G+C content (45.1%). All PCGs started with the typical ATG codon, except COX1, which started with GTG. Seven PCGs ended with incomplete stop codons (TA or T). The Ka/Ks ratios of all PCGs were < 1, indicating purifying selection. The phylogenies of Leiognathidae, both based on the amino acid sequences of the 13 PCGs and the single genes 16S RNA and COX1, were monophyletic with high nodal support (> 75%). L. brevirostris (NC 026232) is believed to be a Nuchequula species, whereas L. ruconius (NC 057225) is not classified under Leiognathus in the NCBI database. The phylogenetic trees divided the Leiognathidae family into three clades. The mitogenome phylogeny suggested that the Leiognathidae and Chaetodontidae clades are sister groups. These findings provide important genetic data for population genetics research and a phylogenetic analysis of Leiognathidae.